Problematyka przemocy w rodzinie w świetle wybranych uregulowań międzynarodowych - Olszewska, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
In the article the problem of domestic violence in the context of legal regulations relating to the protection of human rights is discussed. Reference was made to the historical origins of activities related to the legal protection of fundamental rights and freedoms. A distinction of women’s rights, children and domestic violence in relation to the practice of the United Nations, the Council of Europe and the European Union is considered as a tool to present arguments. The article describes the most important documents regarding the rights of women and children and domestic violence; the rights and duties imposed on signatories in the context of protection of rights and the development of regulations and methods of their implementation referring also to Polish law. The discussion that took place in the public debate prior to ratification of the Convention of the Council of Europe is also touched. The article is an attempt to indicate a significant space they occupy on the issues of domestic violence and their protection in the listed international regulations.
Keywords: przemoc w rodzinie; prawo międzynarodowe; regulacje prawne; prawa podstawowe; prawa kobiet